Osteoporosis prevention in postmenopausal female workers: beneficial effects of silicon dietary supplementation on oxidative status. A pilot study - Vigna, Luisella; De Liso, Federica; Tomaino, Laura; Cighetti, Giuliana; Paroni, Rita; Gestro, Massimo; Ingenito, Maria Rosaria; Napolitano, Filomena; Bamonti, Fabrizia (Progress in Nutrition, 2019)
In the last years, the employment of ageing women is increased, and the well-being of these workers, together with the prevention of chronic disabling diseases, is an issue of great importance. Moreover, as postmenopausal ageing is associated with the loss of bone density and consequent increased fracture risk, promoting bone health in these women could be the best strategy for avoiding osteoporotic fractures. We aimed to evaluate the effects of 3-month supplementation with a commercial antioxidant product containing Silica on oxidative status and bone markers in a sample of Italian female workers. Subjects were menopausal and osteopenic women (N=29, age 59.34±6.37, mean BMI 26.19±4.01 kg/m2). At baseline (T0) and after three-month treatment (T1) bone mineral density (BMD) was evaluated by phalangeal osteosonogrammetry. Haematological, serum biochemical parameters, reactive oxygen species (ROS), total antioxidant capacity (TAC), oxydated low-density lipoproteins (oxLDL) and urinary cross-links pyridinoline (PYD) and deoxypyridinoline (DPD) were assessed. Parametric or non-parametric tests were performed at T0 and T1. To analyse the possible association between two variables a linear correlation test was performed. At T0, slightly high levels of ROS (86% of subjects), oxLDL (59%), Total Cholesterol (T-Chol) (90%) and LDL-Chol (59%) were observed, together with suboptimal or deficient 25-OH vitamin D (98%) concentrations. At T1, oxLDL levels and the ratio oxLDL/LDL-Chol significantly decreased (p<0.01). At T0 significant negative correlations between BMD T-score and cross-links were observed (DPD/Crea: r=-0.57, p=0.001; PYD/ Crea: r=-0.45, p=0.01). At T1, a significant reduction (p=0.03) was observed only for DPD (µg/L) but not for cross-links normalized by creatinine amounts. In conclusion 3-months Silica supplementation improves significantly oxidative status and bone resorption markers in most postmenopausal female workers, representing a complementary treatment for early phases of BMD reduction.